Determinants and catalysts of Silesian regional identity (1526–1740) - Harc, Lucyna (Publishing House eBooki.com.pl, 2014)
The perception of Silesia as something distinct and the formation of emotional bonds with the region, which were based on chronicles from the Middle Ages was further enhanced by humanist thought. Since the end of the 15th century and the beginnings of the 16th due to poetry, historiographical works, geographical description and the first maps, the vision of a region with specified borders, the population of which felt bonded due to shared history, pride of fertile lands and magnificent cities, especially the Capital City of Wrocław the awareness of Silesia as a homeland, simply of being Silesian grew among the population. Boys from different social groups, taught in the local schools were instructed and moulded all through the Habsburg era. Since the Thirty Years’ War, as a result of the policy of undermining the importance of pan-Silesian institutions, with the demise of the Silesian Piast dynasty and other dynasties laying claim on their duchies, the local awareness grew. Even then most authors of historical and cartographical works were aware of the broader context. The identity of being Silesian and the historical continuity of the region since the 10th century, and in the context of the search for ancient origins of the people populating the land even since the biblical times, constituted a factor beneficial to the formation of a cohesive identity, a unifying factor binding coexisting, especially since the 17th century, various local identities.
Keywords: Silesia; school; maps; historiography; patriotism; Piast dynasty; local identity; geographical description; poetry; regional identity